SEJARAH KEPEMIMPINAN KEPALA MADRASAH TSANAWIYAH NEGERI BINTUHAN TAHUN 2000-2014 - M Yusup Azis Yusup Azis (UNIVERSITAS BENGKULU, 2015)
The objective of this research is to describe history of school leadership at Madrasah Tsanawiyah Negeri Bintuhan from 2009 – 2014. The method of this research used history study.The technique of collection data were interview, observation and documentation. Analysis data were data reduction, data display, and conclusion. The conclusions of this research that were thehistorical leadership at Madrasah Tsanawiyah Negeri Bintuhan 2000-2014 met the requirements specified by the standard in accordance with the ministerial regulation no. 13 of 2007. Leadership headmaster from 2000-2014, the history of the journey has reached fourteen years, with a period of fourteen years at Madrasah Tsanawiyah Negeri Bintuhan has happened five times changes of leadership.Key words: leadership, history, headmaster